Moderating role of defensive pessimism in the relationship between test anxiety and performance in a licensure examination - Rob, Rene M. (Animo Repository, 2018)
This study aims to determine if the dimensions of test anxiety, worry, and emotionality, can negatively predict test takers' performance in a licensure examination. It also aims to test if defensive pessimism can buffer these predictive relationships. The study involved 101 individuals who took the Philippine licensure examination for Occupational Therapy and Physical Therapy last February 2017. Results reveal that worry negatively predicts examination performance. However, emotionally turns out to be a positive predictor, after controlling for worry. Furthermore, defensive pessimism weakens the negative effect of worry on examination performance, but did not serve as a moderator in the relationship between emotionality and examination results. Future research directions are further discussed.